2006
DOI: 10.1051/0004-6361:20054493
|View full text |Cite
|
Sign up to set email alerts
|

RASS-SDSS galaxy cluster survey

Abstract: Aims. In this paper we consider a large sample of optically selected clusters, in order to elucidate the physical reasons for the existence of X-ray underluminous clusters. Methods. For this purpose we analyzed the correlations of the X-ray and optical properties of a sample of 137 spectroscopically confirmed Abell clusters in the SDSS database. We searched for the X-ray counterpart of each cluster in the ROSAT All Sky Survey. We find that 40% of our clusters have a marginal X-ray detection or remain undetecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
119
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(139 citation statements)
references
References 79 publications
17
119
3
Order By: Relevance
“…This is not surprising since several authors have observed that optically selected structures have an X-ray emission lower than what is expected from the observations of X-ray selected groups and clusters. This effect has been observed at low redshift in small groups (Rasmussen et al 2006), in Abell clusters (Popesso et al 2007), and in clusters at 0.6 < z < 1.1 (Lubin et al 2004). These results may be explained by the optically selected structures still being in the process of formation or the result of the alignment of two substructures along the line of sight, although it cannot be excluded that they contain less intracluster gas than expected, because of the effect of strong galactic feedback (Rasmussen et al 2006).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This is not surprising since several authors have observed that optically selected structures have an X-ray emission lower than what is expected from the observations of X-ray selected groups and clusters. This effect has been observed at low redshift in small groups (Rasmussen et al 2006), in Abell clusters (Popesso et al 2007), and in clusters at 0.6 < z < 1.1 (Lubin et al 2004). These results may be explained by the optically selected structures still being in the process of formation or the result of the alignment of two substructures along the line of sight, although it cannot be excluded that they contain less intracluster gas than expected, because of the effect of strong galactic feedback (Rasmussen et al 2006).…”
Section: Discussionmentioning
confidence: 59%
“…Dressler et al 1997;Blanton et al 2005;Cucciati et al 2006;Cooper et al 2007;Elbaz et al 2007). Moreover, the analysis of cluster properties at different wavelengths provides interesting insights into the matter content and evolutionary histories of these structures (Lubin et al 2004;Rasmussen et al 2006;Popesso et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The criterion P ≤ 0.1 is commonly used as an indicator for substructures (e.g. Popesso et al 2007). We visualise the possible position of substructures in Fig.…”
Section: Substructurementioning
confidence: 99%
“…Several authors have presented catalogues of rich clusters of galaxies (Aguerri et al 2007;Popesso et al 2007;Miller et al 2005) using the SDSS data. All these group catalogues are constructed on the basis of spectroscopic data, using certain selection criteria.…”
Section: Introductionmentioning
confidence: 99%